Pengaruh Pemberian Madu Terhadap Peningkatan HB Pada Remaja Putri Yang Mengalami Anemia - Afifah Dhiya Ulhaq; Riyanti , Rita (Jurnal Anestesi, 2023)
Background: Adolescents who experience nutritional deficiencies such as iron, calcium, vitamins, magnesium and folic acid can cause anemia. The prevalence rate of anemia in Indonesia in adolescents aged 15-24 years is 32%. The proportion of anemia in women is higher than in men. Honey is a medicine for all kinds of diseases, honey containsl important mineralsl that helpl in thel production ofl hemoglobin. Thenl honey helpsl increase calciuml absorption, hemoglobinl count andl treats or prevents anemial due tol nutritional lfactors. Objective: To determinel the effectl of giving honey onl an increase inl HB inl female adolescents who experience anemia. Methods: The research design was the Pre Experiment and the One Group Pretest Posttest approach, a sample of 23 young girls of class X, the sample used was total sampling. Test analysis using the Paired Simple T Test. The results of the study: The results of the Paired Simple T Test based on HB values before and after being given treatment showed a significant value of 0.000 <0.05 with an average value of an increase of 0.5 gr/dl. Conclusion: Therel is a positive effectl of givingl honey onl the increasel in HB inl female adolescents who experience anemia.